1974
DOI: 10.1111/j.1365-2621.1974.tb17965.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Curing Ingredients and Storage Time on the Quality of Preblended Sausage Meats and Frankfurters

Abstract: S Meats were refrigerated up to 4 days with different salt levels, with and without sodium nitrite and sodium isoascorbate. Franks manufactured from these meats were evaluated during shelf life. Taste testing indicated that frankfurter desirability decreased with meat storage. Salt at 1.5% was effective in inhibiting bacterial growth and caused less rancidification than 3% salt. Franks prepared from meats containing salt and cure remained satisfactory. Cured pigment conversion and residual nitrite levels in fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
1

Year Published

1982
1982
2016
2016

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 17 publications
0
5
1
Order By: Relevance
“…Preblend-holding time influenced pH as there was a decrease (P<0.05) in raw batter pH at 18 hr, however, it seems that pH was not influenced by the 48 hr holding time. This conflicts with previous findings that product pH increased with increased preblendholding time (Ockerman and Crespo, 1982;Sung and Lee, 1985; or remain unchanged with preblend-holding time (Waldman et al, 1974;.…”
Section: Model System Studycontrasting
confidence: 99%
See 1 more Smart Citation
“…Preblend-holding time influenced pH as there was a decrease (P<0.05) in raw batter pH at 18 hr, however, it seems that pH was not influenced by the 48 hr holding time. This conflicts with previous findings that product pH increased with increased preblendholding time (Ockerman and Crespo, 1982;Sung and Lee, 1985; or remain unchanged with preblend-holding time (Waldman et al, 1974;.…”
Section: Model System Studycontrasting
confidence: 99%
“…However, Trout and Schmidt (1983) and reduces the concentration of salt needed for water uptake (Hamm, 1970;Halliday, 1978;Shimp, 1983a, b;Steinhauer, 1983;Tompkin, 1983;Lamkey et al, 1986;Offer et al, 1989). There have been many advantages of preblending reported, but the primary advantage is compositional control (Kramlich, et al, 1973;Waldman et al, 1974;Rust, 1977;Shannon, 1978Shannon, , 1983 product and held at either 0, 4, 8, 12, 24 or 48 hr in his first study, and 0, 4, 8, 12, 16, 48, 96, 144, 192 (Tables 1 and 2). This phenomenon held true for both the fine-cut and coarse-ground products, even though the initial pH of the raw materials used for the coarse-ground sausage was about 0.3 pH units higher than the pH of the raw materials used for the fine-cut sausages.…”
Section: Properties Of Water In Muscle Tissuementioning
confidence: 99%
“…Myofibrillar protein solubilisation thereby increases with increasing ionic strength . The extraction of myofibrillar protein can be enhanced by pre‐blending, which leads to better emulsion stability, firmer texture and characteristic curing colour . The ionic strength may also be sufficiently increased by mixing the meat with only a part of the water …”
Section: Introductionmentioning
confidence: 99%
“…Puolanne and Terrell (1983) found that 4.0% salt in preblends resulted in a higher pH than preblends made with 2.0% salt. Waldman et al (1974) found that meats premixed with sodium nitrite had a significantly (p < .01) higher pH than those mixed with salt alone or salt in combination with sodium isoascorbate. Figure 1 shows the interaction of salt, nitrite, and storage time on the pH of the products.…”
Section: £Hmentioning
confidence: 91%
“…and also with unsaturated carbon-carbon bonds when conditions are similar to those for meat curing. Waldman et al (1974) showed that codium nitrite concentration de creased as storage time increased in preblended sausage meat, but after manufacturing the sausage, there was not much difference in residual nitrite between products with or without preblending. Puolanne et al (1978) reported that meat precured with nitrite had less residual nitrite than normal cured meat.…”
Section: Other Factors Influencing Nitritementioning
confidence: 98%